Posthuman interventions in submerged histories: reconstructing history through memory in Rivers Solomon’s The Deep - Abhishika Dawn; G. Alan (Frontiers in Sociology)
A community’s collective memory is predominantly shaped by dominant power structures that generate and contain canonical narratives. Within the post-colonial context, this social memory remains in conflict with certain ancestral or tribal memories that witnessed the violent legacies of colonization. These memories, which are transmitted across generations—termed postmemory—aims to reclaim and expose the officially silenced histories through the production of counter-memory. Rivers Solomon’s The Deep (2019) explores the historical injustices inflicted upon the African community during the transatlantic slave trade, their impact on successive generations, and the production of counter-memories as a means of resistance and collective catharsis. Solomon crafts a narrative populated by posthuman characters, who in a life-death continuum, embody postmemories and transform their suffering into resistance through the articulation of counter-memories. Through the concept of postmemory, Solomon engages in the process of mourning, simultaneously incorporating counter-memory to call attention to what has been erased from the collective narratives. The paper also seeks to explore the creative reworkings of historical events through posthuman figurations that defy the normative power location of the subject position, highlighting how these concepts intersect to facilitate new avenues for understanding collective experiences of trauma and resilience in the face of systemic erasure.